Anti-arthritic and toxicological evaluation of ethanolic extract of Alternanthera bettzickiana in rats - Manan, Maria; Saleem, Uzma; Ahmad, Bashir; Aslam, Nosheen; Anwar, Asifa; Zafar, Aimen (Frontiers in Pharmacology, 2022)
In many developing countries, medicinal plants have long been used for therapeutic purposes due to their low cost and toxicity. This study evaluated the safety and anti-arthritic potential of Alternanthera bettzickiana ethanolic extract (ABEE). Acute oral toxicity (OECD 425) was tested in the safety evaluation. A limit test was used to identify the LD50 value. For an acute oral toxicity study a dose of 2000 mg/kg of ABEE was given orally to the treatment group, and the control group received distilled water at a rate of 10 ml/kg. Biochemical, hematological, and histopathological analyses were performed after 14 days. A formaldehyde 2% w/v solution was injected via i.p. to rats of all groups to prepare the arthritic model. Five groups were divided into control (D.H2O), standard (Diclofenac), and three groups receiving the plant extract at dose levels of 125 mg/kg, 250 mg/kg, and 500 mg/kg respectively. Treatment was continued for 10 days. Paw diameter and hematological and biochemical variables were quantified. ELISA was performed for the estimation of inflammatory cytokines. In the acute oral toxicity study, no mortality or morbidity were observed, so the LD50 of this plant was greater than 2000 mg/kg. ABEE decreased the paw diameter with the restoration of hematological and biochemical changes. SOD and CAT levels were increased while decreasing the MDA, NO, TNF-α, and IL-6 levels in arthritic rats. It is concluded that the use of A. bettzickiana has low toxicity, and it can be used for the treatment of arthritis.